A systematic review of interventions that use multidisciplinary team meetings to manage multimorbidity in primary care - Greenfield,G (International Journal of Integrated Care, 2022)
Introduction: Multidisciplinary team (MDT) meetings could facilitate coordination of care for individuals living with multimorbidity, yet there is limited evidence on their effectiveness. We hence explored the common characteristics of MDT meetings in primary care and assessed the effectiveness of interventions that include such meetings, designed to improve outcomes for adults living with multimorbidity.Methods: A systematic review of literature was conducted using MEDLINE and EMBASE. A narrative synthesis was performed, extracting study and MDT meeting characteristics, in addition to any outcomes reported.Results: Four randomised controlled trials that were conducted in the United States of America were identified as eligible, recruiting a total of 3,509 adults living with multimorbidity. Common MDT meeting themes include regular frequency of discussion, the absence of patient involvement and the participation of three or four multiprofessionals. Significant improvements were observed in response to interventions with an MDT component across most measures, yet this trend did not extend to physical health outcomes. Discussion: It is unclear if the results in this review are sufficient to support the widespread implementation of MDT meetings in primary care, for adults living with multimorbidity. Due to the paucity of studies collated, further research is required to inform widespread implementation.